2017
DOI: 10.5222/ankem.2017.106
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus, Norovirus and Rotavirus in Etiology of Children with Acute Gastroenteritis Applying to Istanbul American Hospital

Abstract: ÖZET Anahtar sözcükler: adenovirus, akut gastroenterit, norovirus, rotavirus SUMMARY Adenovirus, Norovirus and Rotavirus in Etiology of Children with Acute Gastroenteritis Applying to Istanbul American HospitalThe most common etiologic agents of gastroenteritis in children are rotavirus, norovirus, astrovirus and adenovirus. In the light of the opinion of etiological changes in the frequency of etiology after rotavirus vaccination, cases with viral gastroenteritis in our region and country in our hospital were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[18] Kayıran et al were shown that the incidence of rotavirus gastroenteritis was 3.6% in children with rotavirus vaccination, all of whom were determined to have a high socio-economic status in a private hospital in Istanbul. [19] It is noteworthy that the incidence of rotavirus infections in children with vaccination was lower than those children without vaccination.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[18] Kayıran et al were shown that the incidence of rotavirus gastroenteritis was 3.6% in children with rotavirus vaccination, all of whom were determined to have a high socio-economic status in a private hospital in Istanbul. [19] It is noteworthy that the incidence of rotavirus infections in children with vaccination was lower than those children without vaccination.…”
Section: Discussionmentioning
confidence: 98%
“…In countries with temperate climates like Turkey, rotavirus epidemics occur during colder months of the year, especially during winter as it was in our study, while endemic or sporadic cases occur in other months. In some other studies from Turkey; the majority of the cases were reported to occur in winter and autumn in Duzce, [11] winter and spring in Samsun, [14] spring and winter in Istanbul, [19] spring in Karabuk. [20] In tropical countries, the seasonal variation is less pronounced and rotavirus infections may occur endemically throughout the year.…”
Section: Discussionmentioning
confidence: 99%